SOMDEJ KRU: THE DYNAMIC OF SIAMESE ART TEACHER TRADITION - Sirikul , Prayut; Sirinnakaraporn, Supavee (Journal of MCU Nakhondhat, 2023)
integrated media, as known as the mixed media in the early period of Thai art. This is the dynamic that occurred in both the Western and Eastern worlds, branching out into every aspect of Thai art, especially in fine art through the design of talipot fans and royal ceremonial fans, revealing the design that conveys metaphors, material experiments, and construction in the style that evolved through times. This became a conceptual influence on artists and craftsmen in the next era who followed Somdet Kru's guidelines until the present by maintaining the boundaries of wisdom from the past to the present; and adjusting for the future by combining things from different cultures into one, be it societies, cultures, economies, and technologies. Consequently, the balanced tradition of a Siamese teacher like "Somdej Kru" was constituted. Thus, this is a dynamic that is consistent with history, showing the phenomenon and avenues of national art formation at present and in the future.